2023
DOI: 10.3322/caac.21788
|View full text |Cite
|
Sign up to set email alerts
|

Patient navigation across the cancer care continuum: An overview of systematic reviews and emerging literature

Raymond J. Chan,
Vivienne E. Milch,
Fiona Crawford‐Williams
et al.

Abstract: Patient navigation is a strategy for overcoming barriers to reduce disparities and to improve access and outcomes. The aim of this umbrella review was to identify, critically appraise, synthesize, and present the best available evidence to inform policy and planning regarding patient navigation across the cancer continuum. Systematic reviews examining navigation in cancer care were identified in the Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, Embase, Cumulative Index of Nursing and Allied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(32 citation statements)
references
References 189 publications
(878 reference statements)
0
32
0
Order By: Relevance
“…The review also concluded that most effectiveness and cost-effectiveness data for PN interventions were collected in the United States; therefore, Chan and colleagues call for additional research to evaluate the effectiveness and cost-effectiveness of PN outside of the United States, in survivorship and palliative care phases of the cancer continuum, for indigenous populations, and for individuals affected by rare cancers, hematologic malignancies, as well as advanced or metastatic cancer. 1 Although this review has many important contributions to the literature, there are points that need to be addressed. First, although Chan and colleagues updated the more recent literature, their conclusions do not differ from those of the myriad of other reviews.…”
mentioning
confidence: 99%
“…The review also concluded that most effectiveness and cost-effectiveness data for PN interventions were collected in the United States; therefore, Chan and colleagues call for additional research to evaluate the effectiveness and cost-effectiveness of PN outside of the United States, in survivorship and palliative care phases of the cancer continuum, for indigenous populations, and for individuals affected by rare cancers, hematologic malignancies, as well as advanced or metastatic cancer. 1 Although this review has many important contributions to the literature, there are points that need to be addressed. First, although Chan and colleagues updated the more recent literature, their conclusions do not differ from those of the myriad of other reviews.…”
mentioning
confidence: 99%
“…Indeed, there has been overlap in activities and concepts between "patient navigation," "care coordination," and "case management." 5 Despite the plethora of descriptions and overlapping concepts, we would like to promulgate a definition that has been derived through careful examination of empirical data on implementation and evaluation of patient navigation. A recent extensive review of the literature 5 concluded that patient navigation in cancer care is: an individualized intervention that aims to address barriers and facilitate timely access to healthcare services, diagnosis, and treatments and care, with the following common characteristics: (1) Identifies barriers to accessing care experienced by individuals; (2) Overcomes barriers (eg, healthcare system, literacy, language, cultural, social, financial, and logistical) experienced by individuals; (3) Addresses disparities from contextual barriers (eg, geographical, racial/ethnic, financial, socioeconomic); (4) Can occur anywhere along the cancer care continuum (from early detection to end-of-life); ( 5) Can be delivered by various personnel or through digitalized systems, with or without other facilitators (eg, artificial intelligence).…”
mentioning
confidence: 99%
“…Navigation can also be delivered at an individual level or targeted at a community level, or a combination of both. 5 The American Cancer Society "National Navigation Roundtable," established in 2017, has led a number of initiatives and meetings to advance navigation efforts in the United States. This national coalition published a suite of valuable articles in Cancer in 2022, 4 which address a range of topics relating to progress of the coalition, barriers and opportunities to measuring the impacts of navigation, and implementation concerns and learnings (eg, sustainability, clinical vs nonclinical navigators, role retention, COVID-19 implications).…”
mentioning
confidence: 99%
See 2 more Smart Citations